1994
DOI: 10.2307/4002824
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Quercus Douglasii Removal on Understory Yield and Composition

Abstract: The canopy of Quercus douglasii I-I. & A. (blue oak) has been variously reported to enhance or suppress understory production. The effects of canopy removal have been reported only for the northern portion of blue oak's range. We removed all blue oaks from 6 plots in the central coast of California and found no significant change in understory biomass over 3 years. Understory herb cover averaged 32.6% on cleared plots, compared to 24.3% on uncut plots, but composition changed little with the exception of an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…Indeed, the analyses showed that perturbed areas (P) were associated more particularly with hemicryptophytes, anemochorous and ruderal species; remnant depot (R) areas with seeds dispersed by animals and competitive species; and not perturbed (N) areas with seeds dispersed by wind or animals and stress tolerant species. There was no life form which characterized in particular R or N. As in previous studies [4,20,26,28], we found that hemicryptophytes increased after logging and we specified here that they increased more particularly in perturbed places. These plant species were essentially dispersed by wind and required perturbed areas, without litter, to germinate.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, the analyses showed that perturbed areas (P) were associated more particularly with hemicryptophytes, anemochorous and ruderal species; remnant depot (R) areas with seeds dispersed by animals and competitive species; and not perturbed (N) areas with seeds dispersed by wind or animals and stress tolerant species. There was no life form which characterized in particular R or N. As in previous studies [4,20,26,28], we found that hemicryptophytes increased after logging and we specified here that they increased more particularly in perturbed places. These plant species were essentially dispersed by wind and required perturbed areas, without litter, to germinate.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, the increase of plant species richness after logging was observed by many authors [2,10,20,30,44], as well as after other disturbances like fire and cultural abandonment. [12,37,39,45].…”
Section: Discussion and Concluding Remarksmentioning
confidence: 95%
“…Therophytes and chamaephytes had very low species richness; consequently the data did not allow statistical comparisons. Two years after clear-cut, hemicryptophytes increased significantly (χ 2 (1) = 3.9; p < 0.05), while phanerophytes decreased significantly (χ 2 (1) = 10.6; p < 0.001). Between 1994 and 1998, it was the inverse, hemicryptophytes decreased (χ 2 (1) = 24.0; p < 0.001), while phanerophytes increased (χ 2 (1) = 18.23; p < 0.001).…”
Section: Species Richness In Term Of Life Form and Dispersal Modementioning
confidence: 99%
See 1 more Smart Citation
“…The ecology and management of California's annual grasslands, woodlands, and savannas have been well studied (Bartolome and Standiford 1992, Bartolome and McClaran 1992, Bartolome et al 1994, Heady et al 1992, Standiford et al 1997. However, few studies examine cold-water spring ecosystems of these rangelands, or the potential for grazing effects on them (Allen-Diaz et al 1998).…”
Section: Abstract: Riparian Creek Cover Grazing Species Compositionmentioning
confidence: 99%